Well-controlled silver nanowire/graphene hybrid from full solution process. (April 2017) - Park, Jeong Eon; Suh, Dong Hack
The surface of a one-dimensional silver nanowire was covered with amphiphilic materials, N-(2-aminoethyl)-3a-hydroxy-5b-cholan-24-amide, and patched with two-dimensional graphene to form individually controlled hybrid. Graphene was prepared from ultrasonic in o-dichlorobenzene without any additives. As N-(2-aminoethyl)-3a-hydroxy-5b-cholan-24-amide between silver nanowires and graphene tightly held each other, silver nanowire was individually covered with graphene without introducing ultrasonic power, the necessary process to evenly mix silver nanowires and graphene but lead to damage and oxidize silver nanowires. Although the quality of graphene was inferior, the properties of hybrid were superior compared with pristine silver nanowire/graphene except introducing N-(2-aminoethyl)-3a-hydroxy-5b-cholan-24-amide. All processes to form the hybrid were carried out in solution. Therefore, this makes the processes less expensive and more useful and opens up opportunities for the mass production for conductive materials.